2022
DOI: 10.1055/a-1962-7305
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate- to long-term outcomes of endoscopic transpapillary gallbladder stenting in patients with gallstone-related disease: a 10-year single-center experience

Abstract: Background and study aims: Endoscopic transpapillary gallbladder stenting (ETGS) can be a bridging therapy to elective cholecystectomy or a permanent gallbladder drainage in patients with symptomatic gallbladder disease who are unfit for surgery or have cholecystectomy deferral. We evaluated the intermediate to long-term outcomes of ETGS in these groups. Patients and methods: We retrospectively reviewed 234 patients (acute cholecystitis=147), who were unfit for surgery(n=50) or had deferred cholecystectomy(n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A retrospective monocentric study reported the outcome of 234 patients who underwent TGBD with a single 7 French/15 cm DPS, without scheduled stent exchanges, with a median follow-up period of 564 days (range 200-3001 days). The authors reported a biliary event-free rate of 99% at 6 months, 92% at 1 year, and 76% at ≥2 years, supporting the use of TGBD as definitive treatment in high-risk patients due to a favorable biliary event-free rate at 2 years [52]. Another retrospective study including 49 TGBD reported a long-term clinical success (i.e., no acute cholecystitis recurrence; death or re-interventions at 6 months) of 95.9% (47/49) [25].…”
Section: Therapeutic Strategies After a Successful Endoscopic Gallbla...mentioning
confidence: 79%
“…A retrospective monocentric study reported the outcome of 234 patients who underwent TGBD with a single 7 French/15 cm DPS, without scheduled stent exchanges, with a median follow-up period of 564 days (range 200-3001 days). The authors reported a biliary event-free rate of 99% at 6 months, 92% at 1 year, and 76% at ≥2 years, supporting the use of TGBD as definitive treatment in high-risk patients due to a favorable biliary event-free rate at 2 years [52]. Another retrospective study including 49 TGBD reported a long-term clinical success (i.e., no acute cholecystitis recurrence; death or re-interventions at 6 months) of 95.9% (47/49) [25].…”
Section: Therapeutic Strategies After a Successful Endoscopic Gallbla...mentioning
confidence: 79%
“…These results suggest that advanced age alone should not be a contraindication for LC + LCBDE surgery. Furthermore, studies [ 25 – 30 ] also reported a special intraoperative technique as follows: after the continuous or intermittent suture of the incision site on the CBD was completed, intermittent suture should routinely be added to the surface of this site. This may help reduce tension, which could serve as a reason for reduced biliary leakage [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over a median follow-up period of 564 days, Kaplan-Meier analysis revealed biliary event-free rates of 99% at 6 months, 92% at 1 year, and 76% at ≥2 years. These studies highlight the effectiveness of ETP-GBD as a biliary drainage method for selected patients, especially those unable to undergo cholecystectomy or with deferred cholecystectomy plans [26].…”
Section: Etp-gbd: Technical Success Clinical Success and Additional R...mentioning
confidence: 94%
“…Complications of ETP-GBD include stent migration or occlusion, pancreatitis, postsphincterotomy bleeding, gallbladder injury or perforation, cystic duct injury with potential bile leak, postprocedural pain, pericholecystic fluid collection, and recurrent cholecystitis [6,26,27]. One study found that the cystic duct injury complication had a significant correlation with failure to complete the procedure successfully (Odds ratio [OR] of 11, 95% confidence interval [CI]-3.9-29) [25].…”
Section: Etp-gbd: Complicationsmentioning
confidence: 99%